2019
DOI: 10.2528/pierl19022504
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Band Printed Antenna for Portable Wireless Communication Applications

Abstract: A compact, triple-band (WiMAX, WLAN and X-Band uplink satellite communication) monopole antenna is reported in this paper. The geometry of the proposed antenna consists of a pentagon-shaped patch along with symmetrical hook-shaped resonators and one vertical slot. The reported antenna works at three unique frequencies centered at 3.5 GHz, 5.4 GHz, and 8 GHz, covering absolute bandwidth of 900 MHz (3.2-4.1 GHz), 800 MHz (5.1-5.9 GHz), and 1.6 GHz (7.3-8.9 GHz), respectively. This antenna possesses good gain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A compact monopole antenna with a pentagon-shaped patch, symmetrical hook-shaped resonators, and one vertical slot was already described with the claim that it could be used for many communication modes and could operate at three frequencies (e.g., 3.5 GHz, 5.4 GHz, and 8 GHz). It was found that the antenna was useful for Bluetooth, WLAN, and WiMAX applications [4]. Furthermore, a microstrip patch antenna with a hexagon shape was also demonstrated to support more modes [5].…”
Section: Introductionmentioning
confidence: 99%
“…A compact monopole antenna with a pentagon-shaped patch, symmetrical hook-shaped resonators, and one vertical slot was already described with the claim that it could be used for many communication modes and could operate at three frequencies (e.g., 3.5 GHz, 5.4 GHz, and 8 GHz). It was found that the antenna was useful for Bluetooth, WLAN, and WiMAX applications [4]. Furthermore, a microstrip patch antenna with a hexagon shape was also demonstrated to support more modes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Configurable antennas, in particular, are under the spotlight of researchers with interest in electromagnetic spectrum usage. These antennas can be implemented using a variety of technologies, and the most trending type is the microstrip antennas justified by their low profile, light weight as well as their ability to produce multiple radiation bands [1]- [3]. The rising number of wireless devices is causing spectrum congestion which may increase collisions in the broadcasting channels.…”
Section: Introductionmentioning
confidence: 99%